Chemotherapy-induced cavitating Wilms' tumor pulmonary metastasis: Active disease or scarring? A case report and literature review - Zarfati, Angelo; Martucci, Cristina; Crocoli, Alessandro; Serra, Annalisa; Persano, Giorgio; Inserra, Alessandro (Frontiers in Pediatrics, 2023)
The second most common abdominal tumor in children is Wilms’ tumor, and the lung is where it most often metastasizes. The typical metastases are multiple, peripherally located, round, and variable-sized nodules. Atypical patterns are also possible and may create diagnostic challenges, especially in patients treated with chemotherapy. Among these, cavitating metastases are an anecdotal type of atypical secondary lung lesions. Here, we report a case of a chemotherapy-induced cavitating Wilms' tumor pulmonary metastasis discovered during the follow-up for an anaplastic nephroblastoma in a 6-year-old girl. Furthermore, we conducted a review of the existing literature on this exceedingly rare radiological pattern to establish its best management.